Evaluation of Surfactant Effects on Newborns - Nasrin Khalessi (پزشکی بالینی ابن سینا, 2006)
Introduction & Objective: One of the standard therapies in neonates with severe respiratory distress syndrome (RDS) is surfactant administration in early course of therapy that cause reduction in mortality, pneumothorax and need to mechanical ventilation. In this study that was carried out in Aliasghar Hospital NICU in 1994-1995 & 2001-2002, the goal was to compare two groups of neonates with severe RDS that had been ventilated in the first 24 hours but one group had received surfactant and the other group (7 years ago) was deprived of this substance.